Inter- and intra-rater agreement among novices and comparison to an experienced consensus using the Gächter scale for the evaluation of septic joints - Stockman, Tiffany I.; Kowaleski, Michael P.; Hicks, Jacqueline M.; Berns, Chanel N.; Saunders, W Brian; McCarthy, Robert J. (Frontiers in Veterinary Science, 2025)
IntroductionThe purpose of this retrospective study was to determine the inter-and intra-rater agreement among novice raters, as well as agreement between novice raters and an experienced consensus using the Gächter grading scale for the evaluation of the severity of septic joints in dogs.MethodsThree surgical residents served as novice raters, and two American College of Veterinary Surgery (ACVS) diplomates, experienced with arthroscopic evaluation of canine joints, served as the experienced consensus. Arthroscopy images were first evaluated by the experienced consensus and scored using the Gächter scale. After two supervised training sessions, novices applied the scale twice to the same images, 2 weeks apart.ResultsThe application of the Gächter grading scale was unreliable in dogs when utilized by novice raters.DiscussionBoth the intra-rater agreement measured among the three novice raters and inter-rater reliability comparing the three novice raters to an expert consensus showed a consistently low concurrence among the individuals when tested at two separate time intervals. Lack of skill with arthroscopy, awareness of the anatomy and potential anatomic variations, and inadequate training in the application of the Gächter grading scheme could play a large part in a novice’s ability to apply the grading scale to a septic joint. Inter-rater agreement, while initially moderate, had a decreasing concurrence between the two-time intervals.